(Nie)zwyczajna kremlowska codzienność – Fabien Nury, Thierry Robin: "Śmierć Stalina. Prawdziwa historia… radziecka" - Kowalczyk, Marcin (Załącznik Kulturoznawczy, 2023)
The (Un)ordinary Everyday Reality in the Kremlin: Fabien Nury and Thierry Robin’s The Death of Stalin: A True Soviet Story Daily life is usually associated with repetition and the ordinary. There are, however, settings where the quotidian is far from usual or familiar. Marked by dread and uncertainty, the everyday reality in the Kremlin during Joseph Stalin’s era is one such case evocatively presented in Fabien Nury and Thierry Robin’s graphic novel The Death of Stalin: A True Soviet Story. The article demonstrates how history can be artistically reworked through the comic medium. The analysis focuses on the choice of colors, composition of the panels, perspective, and creation of characters, and refers to the postulates put forward by Hillary Chute, Roland Barthes, and Michel Foucault. The paper concludes that the authors of The Death of Stalin not only offer a convincing take on one of the most crucial moments in the history of the Soviet Union and the world but also employ subtle artistic measures typical of comics to recreate the overwhelming atmosphere of everyday life in the Kremlin dominated by omnipresent fear and uncertainty about the future. The insights they offer into the actions of top-ranking communist officials serve as an artistic commentary on the findings of professional historians, inviting further interpretations.